Molecular characterization of caspase members and expression response to Nervous Necrosis Virus outbreak in Pacific cod. Issue 74 (March 2018) - Mao, Ming-Guang; Jiang, Jie-Lan; Jiang, Zhi-Qiang; Liu, Rui-Ting; Zhang, Qi-Ya; Gui, Jian-Fang
Abstract: Multiple functions of caspases include normal cell turnover, proper development and function of the immune system, hormone-dependent atrophy, embryonic development and chemical-induced cell injury. During artificial propagation of Pacific cod, Gadus macrocephalus, high mortality occurred during early development stages. Here, we performed various analyses on the cDNA and protein sequences of six different G. macrocephalus caspases namely GmCasp3, 6, 7, 8, 9 and 10, and tried to investigate the contributions of caspase family to the development and Nervous Necrosis Virus (NNV) resistance. Sequence analysis of GmCaspase proteins showed that each caspase shared conserved domains like "HG", "QACXG (X for R, G or Q)" and "GSWF" except GmCasp10. Sequence alignment and phylogenetic tree showed that GmCasp8 and GmCasp10 were quite different from those of other fishes. 3-D models indicated that structure of GmCasp3 is very conservative, but GmCasp6, 7, 8, 9 and 10 are less conservative. Tissue distribution analysis showed that six Gmcaspases mRNA transcripts were detected in tissues of intestine, gill, thymus, head-kidney and spleen with different abundance, but Gmcasp7 were not detected in the brain. GmCasp3 transcript was kept at very low level in the early development stages, while the expression levels of GmCasp6, 7, 8, 10 were different at various development stages. GmCasp8 level seemed to be much higher than other caspases in the heads of 65dph and 75dph juveniles. To understand the role of caspases during NNV outbreak, modulation in expression of each Gmcaspases were investigated. The results showed that GmCasp3 transcript level increased significantly when NNV broke out, while GmCasp7, 8, 9 and 10 in cod heads decreased obviously at 69dph and 77dph. The results suggest that caspases in Pacific cod should be diverse in their structure and function, and their unique features and response to NNV outbreak add more evidences for the specificity of immune system in Pacific cod. Highlights: Sequences of caspase-3, 6, 7, 8, 9 and 10 in Pacific cod were obtained. Conserved and uniqueness of Pacific cod caspases were analyzed from sequence alignment and structure modeling aspects. Expression profiles of caspases were examined in various tissues and early developmental stages of Pacific cod. Caspase-3, 6, 7, 8, 9 and 10 were significantly up/down regulated when NNV outbreak.